Математичне моделювання процесів радіально-поздовжнього видавлювання з використанням трапецеїдальних кінематичних модулів - Грудкіна, Н. С.; Hrudkina, N. S. (Кременчуцький національний університет імені Михайла Остроградського, 2020)
З метою дослідження раціональності застосування та особливостей вбудовуваності в загальні розрахункові схеми процесів радіально-поздовжнього видавлювання запропоновано кінематичні модулі трапецеїдальної фо-рми 2b та 2c. Отримано величини приведеного тиску деформування двох розрахункових схем із трапецеїдаль-ними модулями різної форми та кінематично можливими полями швидкостей. Проведено порівняльний аналіз отриманих величин для запропонованих схем і для найуживанішого випадку розбиття на кінематичні модулі прямокутної форми. Виявлено нераціональність використання розрахункової схеми із трапецеїдальним моду-лем 2b з нульовою вертикальною складовою, що пояснюється невдалим вибором кінематично можливого поля швидкостей всередині модуля. Для комбінації із трапецеїдальним модулем 2с із ненульовою вертикальною складовою оптимізація приведено тиску деформування можлива за двома параметрами, що визначають розміри та форму модулів. Використання комбінації із трапецеїдальним модулем 2с замість випадку розбиття на кіне-матичні модулі прямокутної форми є раціональним за будь-яких співвідношень процесу. Завдяки цьому вдаєть-ся досягти зменшення прогнозованої величини приведеного тиску деформування до 7-10%. Отримані результа-ти сприятимуть розробці ефективних розрахункових схем для моделювання процесів із використанням кінема-тичних модулів складної конфігурації, що відображають течію метала, та розробці відповідних технологічних рекомендацій.

Improvement of technologies for cold extrusion processes based on the development of effective calcula-tion schemes for modeling processes by using trapezoidal kinematic modules. Methodology. Based on the prospects of introducing longitudinal-transverse extrusion processes in manufacturing the need to expand the capabilities of the en-ergy method for modeling these processes to assess the power regime is considered. To describe the complex nature of a need to develop a complex of trapezoidal kinematic modules. As an alternative to using the simplest rectangular modules trapezoidal 2b and 2c with a different shape of the boundary and kinematically possible velocity fields is proposed. The values of the reduced deformation pressure in two calculation schemes with the proposed trapezoidal modules, taking into account the presence of adjacent kinematic modules are determined. Results. A comparative analysis of the reduced pressure values for scheme with modules 2b and 2c for the most used partitioning case for kinematic modules of rectangular shape is considered. Irrational use of the design scheme with trapezoidal module 2b with zero vertical component that is explained by the unfortunate choice of the kinematically possible velocity field inside the module is defined. For combination with trapezoidal module, 2с with a nonzero vertical component optimization of the reduced deformation pressure is possible by two parameters determining the size and shape of the modules. Using a combination with a trapezoidal module 2с instead of the case of partition into kinematic modules of rectangular shape is determined in rational for any process ratio. Originality. As a result, the value of the reduced pressure in the developed scheme with trapezoidal module 2с to recommend for use in general design schemes in radial-longitudinal extrusion is considered. Due to this, it is possible to achieve a decrease in the predicted value of the reduced deformation pressure to 7–10%. Practical. The results obtained will contribute to determine an adequate assessment of the power modes in the radial-longitudinal extrusion processes and their wider implementation in manufacturing.
Mathematical modelling of radial longitudinal extrusion process by using trapezoidal kinematic modules
Keywords: комбіноване радіально-поздовжнє видавлювання; математичне моделювання; приведений тиск деформування; combined radial longitudinal extrusion; mathematical modeling; reduced deformation pressure